Role of Alternative Lipid Excipients in the Design of Self-Nanoemulsifying Formulations for Fenofibrate: Characterization, in vitro Dispersion, Digestion and ex vivo Gut Permeation Studies - Alshamsan, Aws; Kazi, Mohsin; Badran, Mohamed M.; Alanazi, Fars Kaed (Frontiers in Pharmacology, 2018)
Background: The choice of lipid excipients and their origin are crucial determinant factors in the design of self-nanoemulsifying drug delivery system (SNEDDS). Aim: To investigate the aspects of alternative excipients which can influence the development of efficient SNEDDS and determine the fate of fenofibrate in aqueous media. Methods: SNEDDS of two groups (a & b) were developed using Cremercoor MCT/ Capmul MCM and Kollisolv MCT/ Imwitor 742 blended oils and water soluble surfactants (to improve lipid polarity) for the model anti-cholesterol drug fenofibrate. Visual assessment was employed and droplet size measurement was taken into initial consideration for optimised SNEDDS. Further SNEDDS optimisations were done on the basis of maximum drug loading by equilibrium solubility studies and maximum solubilised drug upon aqueous dispersion by dynamic dispersion studies. In vitro lipolysis was examined under simulated Fed and Fasted conditions. Intestinal permeability study of the optimal SNEDDS formulation was compared with the raw fenofibrate dispersion using non- everted “intestinal sac technique”. Results: Initial characterisation and solubility studies showed that mixed glycerides of Kollisolv MCT/Imwitor 742 (group b) containing formulations generated highly efficient SNEDDS as they are stable and produced lower nanodroplets with higher drug loading (group b) as compared to mixed glycerides of Cremercoor MCT/Capmul MCM (group a). In vitro dispersion and digestion studies confirmed that SNEDDS of group b (polar mixed glycerides) can retain high amount of drug (99% drug in solution for more than 24 hrs time) in dispersion media and have high recovery after digestion. The results from the permeability assessment confirmed that fenofibrate had 4.3-fold increase with F3b SNEDDS compared with the control. Conclusions: SNEDDS formulations containing alternative excipients (Kollisolv MCT/ Imwitor 742 blend) could be a potential oral pharmaceutical product in taking anti-hyperlipidaemic agent fenofibrate to the systemic circulation as solubilised form.